Centrifugation effect on size distribution of organic dental filler made from glutinous rice flour - Takarini, Veni; Asri, Lia Amelia Tresna Wulan; Djustiana, Nina; Hadi, Bambang Kismono (Faculty of Dentistry Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Organic fillers made from the green-synthesis process can be utilized in dental treatment due to their non-toxic characteristic of the oral environment. Dental fillers must be smaller to improve their mechanical, physical, and biological properties. Material processing and centrifugation contribute to the size of processed materials. This study evaluates the effect of different centrifugation speeds on the size and distribution of glutinous rice flour as organic dental filler. Methods: This experimental study uses glutinous rice flour suspended in water and then centrifuged at different speeds of 3000 and 6000 rpm compared to untreated glutinous rice flour as control. The particle size was examined using Scanning Electron Microscope (SEM) and Dynamic Light Scattering (DLS). Next, Fourier Transform Infra Spectroscopy (FTIR) and X-ray Diffraction (XRD) were performed to evaluate whether there were structure and crystallinity changes. Finally, the cytocompatibility of fillers was examined by a cell viability test. Results: Centrifugation of glutinous rice flour at 3000 rpm resulted in smaller average size particles, evenly distributed, and higher crystallinity than other groups. There were no changes in functional groups, as shown by FTIR spectra. However, the processed samples were more amorphous compared to the control. Importantly, the processed samples appeared to be non-toxic, with a range of cell viability of 82.75-86.67% after 24 h incubation. Conclusion: Centrifugation speed of 3000 rpm has decreased in size, and a more homogenous particle size of organic filler made from glutinous rice flour. Importantly, it improved the cytocompatibility of particles compared to untreated control. Altogether, we proposed this organic material as a new potential material in the dental application that can be further investigated. Keywords: centrifugation speed; size distribution; organic dental filler; glutinous rice flour